Hereditary Hemorrhagic Telangiectasia with Hepatic Vascular Malformations - Yujiro Nishioka; Nobuhisa Akamatsu; Yasuhiko Sugawara; Junichi Kaneko; Junichi Arita; Yoshihiro Sakamoto; Kiyoshi Hasegawa; Norihiro Kokudo (Case Reports in Medicine)
Hereditary hemorrhagic telangiectasia (HHT) is a rare autosomal dominant hereditary disease. Early diagnosis is important to avoid complications from vascular lesions, but diagnosis is difficult in asymptomatic patients. A 69-year-old Japanese male patient was referred to our hospital for evaluation of hepatic vascular malformations. He had mild anemia with iron deficiency, and dynamic contrast-enhanced computed tomography revealed significant arteriovenous and arterioportal shunts throughout the liver. Telangiectasia from the pharynx to the duodenum was confirmed by gastrointestinal endoscopy. The patient history revealed episodes of epistaxis as well as a family history of epistaxis. He was diagnosed with HHT, although no other family member had been diagnosed with definite HHT. A diagnosis of HHT must be considered in patients with hepatic vascular malformations.